Appreciate fallen heroes who fought communists, youth told - Kalbana, Perimbanayagam; Muhammad, Aizzuddin (New Straits Times Press (M) Bhd., 2022)
KUALA LUMPUR: Malaysians live in peace today thanks to the sacrifices and perseverance of the forefathers of the police force.